PENGARUH KEMAMPUAN DAN MOTIVASI TERHADAP KINERJA PEGAWAI DINAS SOSIAL KOTA DUMAI - Susi Hendriani; Rendra Wasnuri; Juli Hendra Asmoro (Fakultas Ekonomi dan Bisnis, Universitas Riau, 2013)
The research was conducted on the Social Service Employees Dumai City with theaim to analyze the influence of variables on the performance ability andmotivation of Social Service Employees Dumai City. The purpose of this studywas to determine the to determine the influence of ability and motivation on theSocial Service Employee Dumai City’s performance.Sampling was carried by census method with the whole population asrespondents, 23 peoples. Analytical methods used are qualitative descriptivemethods, and techniques of data collection is done by using interviews andquestionaires to the overall respondents.From the results obtained that motivation variable was the most dominant factor,with an average at 3,98 which is more higher than the average rate of capacityvariable at 3,64. The recommendation can be given by the author is Dumai CitySocial Service Agency should give more attention to the work ability of employeeby improving the implementation of technical training and the motivation ofemployee should be considered and demand more productivity so that any job isdone maximally, and also the evaluation of employee should be done closely togive more higher performance quality of the employee.Kata Kunci : Ability, Motivation and Employee’s performance